Generation and Utilization of Volatile Fatty Acids and Alcohols in Hydrothermally Altered Sediments in the Guaymas Basin, Gulf of California. Issue 5 (4th March 2019) - Zhuang, Guang‐Chao; Montgomery, Andrew; Samarkin, Vladimir A.; Song, Min; Liu, Jiarui; Schubotz, Florence; Teske, Andreas; Hinrichs, Kai‐Uwe; Joye, Samantha B.
Abstract: Volatile fatty acids (VFAs) and alcohols are key intermediates of anaerobic carbon metabolism, yet their biogeochemical cycling remains poorly constrained in hydrothermal systems. We investigated the abundance, stable carbon isotopic composition, and metabolic cycling of VFAs and alcohols to elucidate their generation and utilization pathways in hydrothermally influenced sediments (4 °C to 90 °C) from the Guaymas Basin. Acetate (up to 229 μM) and methanol (up to 37 μM) were abundant in porewaters. The δ 13 C values of acetate varied between −35.6‰ and −18.1‰. Carbon isotopic signatures, thermodynamic predictions, and experimental incubations suggested biological sources such as fermentation and acetogenesis for acetate. Acetate and methanol were predominantly consumed by nonmethanogenic processes (e.g., sulfate reduction), as reflected in high oxidation rates versus low methanogenesis rates, and further evidenced through inhibition experiments with molybdate. These results reveal an important role for VFAs and alcohols as energy sources for diverse chemoheterotrophs in organic‐rich hydrothermally influenced sediments. Plain Language Summary: Hydrothermal systems are unique seafloor habitats that host abundant and diverse microbial communities, but questions remain regarding their energy strategy and metabolic activity. We found that low molecular weight organic compounds such as acetate and methanol were abundant in the hydrothermal sediments of Guaymas Basin. Multiple lines of evidence suggested that these substrates were produced largely via biological pathways. We further investigated the microbial metabolism of acetate and methanol and found that both compounds could be used as an energy source to support various microbial processes in the hydrothermal systems. Key Points: Volatile fatty acids (VFAs) and alcohols were abundant in the hydrothermal sediment of the Guaymas Basin Isotopic signatures, thermodynamics, and sediment incubations suggest that the source of VFAs is biological fermentation and acetogenesis High oxidation rates of acetate and methanol document utilization predominantly by nonmethanogenic chemoheterotrophs as an energy source